Народний рух України у документально-речовій збірці Національного музею історії України (до 30-річчя створення громадсько-політичної організації) - Срібна, М. (Краєзнавство, 2019)
У статті показано документально-речову колекцію Народного руху України (НРУ), яка зберігається в Національному музеї історії України. Завдяки фондовому зібранню можна простежити важливі сторінки діяльності НРУ в кін. 1980-х рр. – на поч. 1990-х рр. The National Museum of the History of Ukraine is a leading establishment in the country. The article shows a documentary collection of the People’s Movement of Ukraine, which is stored in the National Museum of the History of Ukraine. Thanks to the stock meeting you can trace important pages in the activities of the People’s Movement of Ukraine in the end 1980 – the beginning 1990 years. Initially organized as the People’s Movement of Ukraine for Reconstruction was founded in 1989 as a civil-political movement as there were no other political parties allowed in the Soviet Union but the Communist Party. The first Constituent Congress of the People’s Movement of Ukraine for Reconstruction took place on 8–10 September 1989 in Kyiv. Elected as the first leader of the movement was the Ukrainian poet and screenwriter Ivan Drach. At first the movement aimed at supporting Gorbachev’s reforms, later the People’s Movement of Ukraine was instrumental in conducting an independence referendum in the Ukrainian SSR. The collection of the National Museum of the History of Ukraine makes possible to carry out significant research and educational work on the history of Ukraine.